Does bank credit mitigate nature and climate change effects in cereal production - Peter Simiyu Wamalwa; Anne Kamau; Maureen Odongo; Roseline Nyakerario Misati (Kenya Bankers Association (KBA), 2025)
The study analyzed the relationship between climate change, bank credit, and cereal production in Kenya based on quarterly data covering the period 2000-2023 using autoregressive distributed lag approach. The study used CO2 emissions, average precipitation, and average temperature as indicators of climate change and private sector credit and credit to agriculture sector as indicators of bank credit. The empirical findings show that there is a long-run relationship between cereal production and banks' domestic credit, CO2 average precipitation, average temperature, and cereal production area. The results also indicate that bank credit, average precipitation and increase in cereal production area stimulate cereal production, while CO2 emissions and average temperature reduces cereal production in the long run. In the short run, precipitation, bank credit, mechanization increase cereal yield, while CO2 emissions and acreage under cereal cultivation, and average temperature reduce cereals production. The increase in CO2 emissions and average temperature interfere with growth and development of plants and hence the yields. However, bank credit enables farmers to counteract the impacts of climate change as it facilitates purchase of farm inputs, which in turn boost cereal production. These findings imply that there is need to mitigate climate change, because it has adverse impact on cereal production. There is also a need to enhance lending to the agriculture sector so that farmers can boost cereal production, enhance capacity to mitigate climate change as well as wither the impact of climate change on cereal production.
Keywords: 330; Bank Credit; Climate Change Risk; Cereal Production